2023
DOI: 10.1126/sciadv.adh9570
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor neurons in the dorsomedial hypothalamus input to the circadian feeding network

Qijun Tang,
Elizabeth Godschall,
Charles D. Brennan
et al.

Abstract: Salient cues, such as the rising sun or availability of food, entrain biological clocks for behavioral adaptation. The mechanisms underlying entrainment to food availability remain elusive. Using single-nucleus RNA sequencing during scheduled feeding, we identified a dorsomedial hypothalamus leptin receptor–expressing (DMH LepR ) neuron population that up-regulates circadian entrainment genes and exhibits calcium activity before an anticipated meal. Exogenous leptin, silencing, or chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 119 publications
1
2
0
Order By: Relevance
“…S3G). However, the Glp1r DMH neurons in our study also expressed the leptin receptor gene, Lepr, and so may correspond to a previously identified population of DMH inhibitory neurons which co-express Glp1r and Lepr 85 . Lepr+ DMH neurons inhibit AgRP neurons in response to external food cues to reinforce food-seeking behavior 18,86 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…S3G). However, the Glp1r DMH neurons in our study also expressed the leptin receptor gene, Lepr, and so may correspond to a previously identified population of DMH inhibitory neurons which co-express Glp1r and Lepr 85 . Lepr+ DMH neurons inhibit AgRP neurons in response to external food cues to reinforce food-seeking behavior 18,86 .…”
Section: Discussionsupporting
confidence: 76%
“…One possibility is that the Glp1r + DMH neurons rapidly inhibit AgRP neurons in response to external food cues, as previously reported of DMH Lepr + neurons 17 , potentially to reinforce food-seeking behavior (Berrios et al, 2021). Accordingly, a recent single-cell RNA-seq analysis of DMH neurons showed that expression Glp1r and Lepr are highly co-localized 70 . However, unlike the Lepr + DMH neurons, the Trh Arc neurons characterized in our study received little if any synaptic input from the lateral hypothalamus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DMH LepRb neurons that project to the suprachiasmatic nucleus exhibit calcium activity prior to an anticipated meal. These neurons serve as a crucial link between the metabolic and circadian systems, thus facilitating mealtime anticipation (Tang et al, 2023). The sympathetic nervous system (SNS) mediates the cardiovascular and thermogenic effects of leptin within the DMH.…”
Section: Role Of the Dmh In Mediating The Effects Of Leptin On Energy...mentioning
confidence: 99%